1985
DOI: 10.1111/j.1365-2621.1985.tb10459.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gamma Irradiation on Proteins and Fatty Acids of Soybean

Abstract: Two hundred grams of soybean seeds (moisture contents of 7.4, 15.3, 22.5, and 30.5%) were irradiated at dose levels of 0, 1, 5, 10, 20, 40, 60, 80 and 100 KGy using Cobalt-60 source. Radiation dose of 100 KGy caused a decrease in the percentage of nitrogen solubility from 80.3 to 67.2, 80.3 to 57.8, and 68.1 to 48.8 when deionized H20, 0.6M NaCI, and 0.2M Caclz were used as solvents, respectively. Inhibition of 71% of lipoxygenase activities, 25.4% trypsin inhibitor activities, and 16.7% chymotrypsin inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
1
5

Year Published

1991
1991
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 20 publications
3
18
1
5
Order By: Relevance
“…These results are in agreement with the results obtained by several investigators (Shahin, 1993, Mohsen, 1996, Mahrous, 2007, who reported that a marked decrease in iodine value was noticed for irradiated soybean, sesame and cotton seed oil and the decrease was proportional to the irradiation doses. The obtained results confirm that irradiation accelerates the autoxidation process in unsaturated fatty acids in the presence of oxygen through the formation of free radicals and causes the breakdown and destruction of the antioxidants and change the chemical constituents of the lipid fraction (Hafez et al, 1985, Nawar, 1978. A.M.R.…”
Section: Peanut Seedssupporting
confidence: 63%
“…These results are in agreement with the results obtained by several investigators (Shahin, 1993, Mohsen, 1996, Mahrous, 2007, who reported that a marked decrease in iodine value was noticed for irradiated soybean, sesame and cotton seed oil and the decrease was proportional to the irradiation doses. The obtained results confirm that irradiation accelerates the autoxidation process in unsaturated fatty acids in the presence of oxygen through the formation of free radicals and causes the breakdown and destruction of the antioxidants and change the chemical constituents of the lipid fraction (Hafez et al, 1985, Nawar, 1978. A.M.R.…”
Section: Peanut Seedssupporting
confidence: 63%
“…Maxwell and Rady (1989) also reported a steady increase in oleic acid in the polar fractions with increasing doses of gamma irradiation. However, Hafez et al (1985) did not find changes in the fatty acids (C16:0, C18:1 and C18:2) of soybeans at different radiation doses (1,5,10,20,40,60,80 and 100 kGy). Katta et al (1991) found significant decrease in amount of Palmitic acid and increase in oleic acid as irradiation dose level increased (0.5-3 kGy) in chicken meat.…”
Section: Discussionmentioning
confidence: 91%
“…Changes in the palmitic (C16:0), oleic (C18:1) and linoleic (C18:2) fatty acids of soybeans at different radiation doses (1, 5, 10, 20, 40, 60, 80 and 100 kGy) were no found (Hafez et al,1985). The irradiation at 10 kGy also changes the linoleic and linolenic acid contents of grass prawns.…”
Section: Type Of Food Effect Of Irradiationmentioning
confidence: 83%